Runway Pavement Design using the Federal Aviation Administration Method - Yulfah, Gebi Aini; Sholichin, Ibnu; Utomo, Nugroho (CIVED, 2023)
Dhoho International Airport is a new airport located in Kediri Regency, East Java Province, which is built on an area of + 454.5 hectares with a runway length of 3300 m and a width of 45 m. According to its hierarchy, Dhoho Kediri International Airport is a feeder airport (spoke). The B777-300ER aircraft is planned to operate at Dhoho International Airport with a plan life of 10 years which has a subgrade CBR value of 6%. The purpose of this research is to determine the thickness of flexible pavement on the runway of Dhoho Kediri International Airport using the FAA method. In determining the thickness of the runway flexible pavement using the FAA method is influenced by the number of annual departures of aircraft, the MTOW value of aircraft and the CBR value of the subgrade. To determine the annual number of aircraft departures at the new airport, it is necessary to forecast the number of passengers by considering the number of passengers at the nearest airport. Based on data analysis in this study, the total thickness of runway flexible pavement at Dhoho International Airport using FAA method is 102 cm with details of surface thickness of 13 cm, base course thickness of 56 cm, and subbase thickness of 33 cm.